Kuwait's Leadership In Mediation Of The Gave State Diplomic Conflict 2017-2019 - Yus, Agung Qosym; Hannase, Mulawarman (UI Scholars Hub, 2022)
The Gulf region in 2017 experienced a diplomatic crisis that was quite complicated so that it could be said as a regional conflict which was manifested in the form of a blockade and the closure of diplomatic relations between them. This crisis mainly involves Saudi and its allies to blockade Qatar in various ways. This conflict made Kuwait emerge as a mediator trying to restore the diplomatic situation in the Gulf region back to normal. By using literature studies and qualitative research methods in analyzing the data, it can be seen that Kuwait succeeded in neutralizing and slowly returning to the situation in the Gulf region to open the blockade and re-establish diplomatic relations with Qatar. So it can be concluded that Kuwait formed a narrative of “solidarity” and “stability” to reconcile the conflict situation.